Potassium hydroxide modification and characterization of nano-zinc oxide in methanolysis of rice bran oil - Suleiman Kabo, Kamaluddeen (2016)
Biodiesel is an alternative biofuel that could help to reduce the use of fossil fuels and protect the environment. However, its production is still challenged by catalyst development, evaluation and process optimization. In this research, new structure and base modified zinc oxide nanocatalysts were prepared and used in the methanolysis of rice bran oil (RBO). The catalysts were characterized by field emission scanning microscope (FESEM), powder X-ray diffraction (XRD), nitrogen adsorption, Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray fluorescence (XRF) and basic concentration back titration analyses. While, biodiesel was characterized by proton nuclear magnetic resonance spectroscopy (1H NMR) and gas chromatography flame ionisation detector GC-FID method. The results showed that different nanoparticles were successfully prepared from direct precipitation; nanoflowers and nanotubes attained through hydrothermal methods without the use of any surfactant or templating agent. The synthesized nanostructures were base-modified using KOH by wet impregnation using Response Surface Methodology-Box Behnken Design (RSM-BBD) method. It was observed that nanoparticles and nanotubes have the lowest crystallite sizes of 34.32 and 29.96 nm, are mesoporous in nature, having open ended tubular pores with BET surface areas of 12.82 and 14.29 m2g-1, pore sizes of 46.93 and 42.57 nm and pore volumes of 0.1315 and 0.1475 cm3g-1, respectively. The XRD, nitrogen adsorption and FTIR analyses showed the presence of K as substituent in ZnO lattices after modification, which was confirmed by XPS with proposed molecular formula as Zn(1-x)KxO and supported by XRF indicating the atomic weight percentage as 2.24%. Although both structure and base modification affect the basic sites concentration, but base modification has more influence, the K-modified ZnO nanotubes having the highest basic sites of 8.82 mmol/g. The RSM was used for the methanolysis experimental design and optimization. Analysis of biodiesel products shows the highest biodiesel yield of 96.24% in 90 min was observed from K-modified nanotubes, followed by nanoparticles, 95.95% in 120 min and nanoflower 94.82% in 120 min. Catalyst loading of 3.7%, methanol to oil ratio 1:9 and temperature of 65oC was used as the optimum conditions. Results from catalyst reusability and leaching tests show that among the nanostructures, K-modified nanotubes undergo minimum leaching and the highest recyclability. Thus, structure modification using simple growth and impregnation methods helped in the preparation of efficient basic transesterification catalysts, such that the nanotubes are the best catalysts, which demonstrated high biodiesel yield and stability for use at relatively lower reaction conditions.